2014
DOI: 10.1080/00220388.2014.928698
|View full text |Cite
|
Sign up to set email alerts
|

How Vulnerable are Arab Countries to Global Food Price Shocks?

Abstract: We estimate pass-through effects of international food price movements into domestic food prices for eighteen countries in the Middle East and North Africa, using threshold regressions. International price movements transmit to various degrees into domestic prices. Transmission is mostly asymmetric, pushing domestic price levels up, as increases in international food prices are typically passed through, but declines are rarely transmitted. This situation is indicative of policy and market distortions, notably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
3
24
0
1
Order By: Relevance
“…The short-run adjustment pattern in their case exhibited asymmetries and was particularly strong after positive shocks. The studies [23,24] also found that global food inflation is an important source of inflationary pressures in the MENA region. Based on reduced-form VARs, the authors in [25] concluded that international commodity price inflation is the main determinant of producer and consumer food price inflation in the Euro area, with a pass-through coefficient of 0.3.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-run adjustment pattern in their case exhibited asymmetries and was particularly strong after positive shocks. The studies [23,24] also found that global food inflation is an important source of inflationary pressures in the MENA region. Based on reduced-form VARs, the authors in [25] concluded that international commodity price inflation is the main determinant of producer and consumer food price inflation in the Euro area, with a pass-through coefficient of 0.3.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evidence is scarce for MENA countries. Following [23], a 1% increase in global food prices raises domestic food prices by 0.2-0.4%. For some countries, such as Egypt and Morocco, the price transmission exhibits significant asymmetries, as price increases have stronger absolute effects on domestic inflation than price decreases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, a Bayesian approach was used to estimate the quantile regressions instead of the classical approach of Koenker (2005) or the GMM approach of Meniago and Asongu (2018). The Bayesian approach was adopted in order to explicitly take into account the uncertainty about inequality and inflation in the MENA region: Commander 2017indicated that due to a lack of transparency, inequality may be higher than reported in this region, and Ianchovichina et al (2014) highlighted that in MENA countries inequality measures are based on household surveys that suffer from several well-known shortcomings as, e.g. survey respondents that under-report expenditures or deliberately leave out income from illegal or informal activities.…”
Section: Bayesian Quantile Regressionmentioning
confidence: 99%
“…survey respondents that under-report expenditures or deliberately leave out income from illegal or informal activities. Also, according to Ianchovichina et al (2014), household surveys in MENA countries only include a few individuals at the very top of the income distribution, which limits accurately capturing the top 1 percent population that is crucial to estimating inequality. In relation to inflation, in MENA countries this variable can be underestimated if there is a deterioration of the quality of the products in the reference basket or if the mix of goods and services is not updated to reflect changes in preferences (Ianchovichina et al, 2014).…”
Section: Bayesian Quantile Regressionmentioning
confidence: 99%
See 1 more Smart Citation